1992
DOI: 10.1111/j.1524-4725.1992.tb03220.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory Aspects of Venous Ulceration

Abstract: BACKGROUND. Articles were identified from a literature search based on Index Medicus from 1983 onwards with additional, as yet, unpublished data obtained directly from ongoing research at The Middlesex Hospital Vascular Laborato y. Original scientific articles were selected if they addressed the mechanisms causing venous ulceration in relation to the events in the microcirculation. OBJECTIVE. To review the mechanisms proposed recently to explain the pathogenesis of venous Ulceration. RESULTS. Recent data sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…10,33 Sustained hypertension at the capillary level is associated with many morphologic changes including elongation and dilation of the capillary bed, increased surface area of the endothelium, increased type IV collagen in the basement membrane, and the formation of a pericapillary fibrin cuff. 12,[34][35][36][37] These abnormal capillaries are more permeable to large molecules, including fibrinogen, 38 and it has been hypothesized that leaked fibrinogen is converted to fibrin in the pericapillary space. 37,38 Other studies have shown that the fibrinolytic activity of blood and tissues is deficient in patients with lipodermatosclerosis, resulting in a decreased clearance of fibrin.…”
Section: Pathophysiologymentioning
confidence: 99%
“…10,33 Sustained hypertension at the capillary level is associated with many morphologic changes including elongation and dilation of the capillary bed, increased surface area of the endothelium, increased type IV collagen in the basement membrane, and the formation of a pericapillary fibrin cuff. 12,[34][35][36][37] These abnormal capillaries are more permeable to large molecules, including fibrinogen, 38 and it has been hypothesized that leaked fibrinogen is converted to fibrin in the pericapillary space. 37,38 Other studies have shown that the fibrinolytic activity of blood and tissues is deficient in patients with lipodermatosclerosis, resulting in a decreased clearance of fibrin.…”
Section: Pathophysiologymentioning
confidence: 99%
“…3,4 As a result, blood flow velocity in the microcirculation decreases, which in turn favours the adhesion of leukocytes to the capillary walls (the leukocyte trap theory). [5][6][7] The trapped leukocytes damage the capillaries (they cause increased permeation of leukocytes through the vein walls to the surrounding tissue 6 ) and lead to local hypoxia. In a hypoxic environment the leukocytes are stimulated and release various substances: cytokines (mainly alpha-tumor necrosis factor, interleukins), leukotrienes and proteolitic enzymes (elastase, collagenase).…”
Section: Introductionmentioning
confidence: 99%
“…10,33 Sustained hypertension at the capillary level is associated with many morphologic changes including elongation and dilation of the capillary bed, increased surface area of the endothelium, increased type IV collagen in the basement membrane, and the formation of a pericapillary fibrin cuff. 12,[34][35][36][37] These abnormal capillaries are more permeable to large molecules, including fibrinogen, 38 and it has been hypothesized that leaked fibrinogen is converted to fibrin in the pericapillary space. 37,38 Other studies have shown that the fibrinolytic activity of blood and tissues is deficient in patients with lipodermatosclerosis, resulting in a decreased clearance of fibrin.…”
Section: Pathophysiologymentioning
confidence: 99%